2021
DOI: 10.1111/aor.13952
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CytoSorb on kinetics of vancomycin and bivalirudin in critically ill patients

Abstract: CytoSorb is a promising tool to treat severe inflammatory status with multiple mechanisms in the acute care setting. Its effect on drugs is, however, poorly documented in vivo, although removal of small molecules might translate into decreased blood levels of life‐saving medications. The aim of this study was to assess the impact of CytoSorb on vancomycin and bivalirudin clearance in a large population of critically ill patients. We performed a single‐center analysis of CytoSorb treatments performed between Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 20 publications
(32 reference statements)
3
16
0
Order By: Relevance
“…Indeed, all patients were intubated and 53% were under VV ECMO due to refractory respiratory failure. In line with existing reports, 5 CytoSorb treatment was effective in improving several laboratory parameters (biliribubin above all) in our experience and no treatment-related adverse effects were recorded. The rationale for the use of CytoSorb in shock of several origin has been stressed in literature, with possible outcome benefits.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, all patients were intubated and 53% were under VV ECMO due to refractory respiratory failure. In line with existing reports, 5 CytoSorb treatment was effective in improving several laboratory parameters (biliribubin above all) in our experience and no treatment-related adverse effects were recorded. The rationale for the use of CytoSorb in shock of several origin has been stressed in literature, with possible outcome benefits.…”
Section: Discussionsupporting
confidence: 92%
“…CytoSorb treatment (CytoSorbents Corporation, NJ, USA) is gaining increasing attention as a promising therapeutic tool in several acute care settings, [3][4][5] alone or in combination with other extracorporeal devices. 4,5 Following our previous experience with cytosorb treatment in intensive care unit patients, 4,5 we decided to use CytoSorb therapy in patients critically ill due to SARS-CoV-2 syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the in vitro data, there is only limited clinical data: Dimski et al demonstrated a significant adsorption and a superiority of the continuous infusion in two patients with vancomycin therapy and simultaneous CytoSorb ® application [ 19 ]. Scandroglio et al retrospectively showed an increased daily vancomycin dose requirement of about 500 mg in 89 critically ill patients [ 20 ]. Unfortunately, no population pharmacokinetic approach was applied in either study, so that a quantitative evaluation and comparability to our study is not possible without restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is the interaction between CytoSorb ® and vancomycin. However, there is a lack of reliable clinical data supporting the adsorption of vancomycin by CytoSorb® [ 19 , 20 ]. As a consequence, intensified TDM of antibiotics was recommended during the use of CytoSorb ® , although this service is sometimes not available, especially during weekends [ 4 , 11 , 17 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its effects are wide and can be more properly assessed in terms of shock control (eg, reduction of inotropic requirements and shock laboratory parameters). 3 Moreover, patients on ECMO rarely benefit from or are rarely harmed by a single treatment: outcome is the result of comprehensive intensive management, by which the strategy of therapy is supported by mechanical circulatory support and associated devices. The reported causes of death reflect the importance and outcome of intensive care in general (including more than 6 L of fluids per patient) rather than device-related thromboembolic complications.…”
mentioning
confidence: 99%